2021
DOI: 10.3390/horticulturae7100396
|View full text |Cite
|
Sign up to set email alerts
|

The Utilisation of Pholiota nameko, Hypsizygus marmoreus, and Hericium erinaceus Spent Mushroom Substrates in Pleurotus ostreatus Cultivation

Abstract: The feasibility of utilising spent mushroom substrates (SMSs) as a growing medium component for Pleurotus ostreatus cultivation was investigated. P. ostreatus was cultivated on traditional wheat straw (control) and wheat straw substrate supplemented with SMSs from Pholiota nameko (N-SMS), Hypsizygus marmoreus (M-SMS), and Hericium erinaceus (E-SMS) in varying supplementation rates (10%, 20%, and 30%). The yield, biological efficiency (BE), dry matter, and protein content of P. ostreatus fruiting bodies grown o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Increases in available carbohydrates, ash and others, such as nitrogen, are interesting for the reuse of these substrates in animal feed (Ivarsson et al, 2021), in a new mushroom cultivation (Lisiecka, Prasad;Jasinska, 2021), or as a bio-fertilizer (Carmo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Increases in available carbohydrates, ash and others, such as nitrogen, are interesting for the reuse of these substrates in animal feed (Ivarsson et al, 2021), in a new mushroom cultivation (Lisiecka, Prasad;Jasinska, 2021), or as a bio-fertilizer (Carmo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In several cases, similar [ 27 , 29 , 40 , 44 , 50 ] or even higher [ 26 , 28 , 45 ] values of biological efficiencies (ΒΕ; percentage ratio of fresh mushroom weight over the dry weight of the respective substrate) were recorded in substrates containing SMS deriving from the cultivation of either the same or other mushroom species when compared to conventional (used for the first time) substrates. However, in some studies, it was also reported that the incorporation of high amounts of SMS in the new cultivation medium or the casing layer negatively affected the mushrooms’ final yield [ 30 , 36 , 37 , 42 ], which could be mainly attributed to the low content of nutrients or to inadequate supplementation of the spent substrates.…”
Section: Reusing Spent Mushroom Substrate For New Cultivation Of Mush...mentioning
confidence: 99%
“…Several studies have demonstrated the possible cultivation of Pleurotus spp. on non-traditional substrates, including spent mushroom substrate [21], agave bagasse [22], olive-mill wastes [23], winery and olive will waste [24], rice-bran and food waste compost [25] as well as anaerobically digested plant and agro-residues [26]. The cultivation of Pleurotus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The cultivation of Pleurotus spp. on straw-based and other agro-waste-derived substrates has been extensively studied [11,18,27,28], while the scientific reports on utilising non-traditional substrate substitutes derived from neglected waste streams, for instance, spent mushroom substrates [21] or combined dairy manurefood waste digestate [20], for mushroom cultivation is still in their infancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation